Open Theism and Prophecy - Yöney, Ferhat (Sophia, 2025)
Open theists defend the epistemic openness of the contingent future for God, although they don’t regard biblical prophecies, which involve God’s providing information about the future, as problematic for their view. They proceed to explain such prophecies in one of the following three ways: as conditional prophecies, as prophecies based on current necessities, or as prophecies of divine intentions. In this article, I argue that there are problematic biblical prophecies for open theism that can’t be explained in any of these three ways within an open theist framework. Then I propose two ways for open theists to deal with these problematic prophecies. The first solution is to renounce a literal interpretation of the problematic prophecies, which would be compatible with open theism being more biblical than its rivals. The second solution is to put forward a fourth way of explaining prophecies, which involves a specific view of future contingents, and to apply it to the problematic prophecies.